Cussy de Almeida Neto: sua influência como violinista e compositor na música nordestina de concerto - Carvalho, Emmanuel Wilson de (2023)
This research proposes to preserve the memory of the music contributions from Cussy de Almeida Neto, who is violinist and composer. It will talk about his career as a violinist, his influence on northeastern concert music, and his artistic legacy as a performer and composer on Brazilian music in the second half of the 20th century. For this, follow some important specific objectives: to identify the objectives that inspired Almeida create the Armorial Orchestra; to present his influence as a violinist and composer; to outline the musical aesthetics created in Northeastern Concert Music and developed in the Armorial Orchestra. This research is presented in three parts: first, an overview of all research material, then the organization of the texts and works, and finally the written presentation of the result. In order to achieve the research objectives of this work, which is a documentary and bibliographical study, the search was made in the author's personal collection, the discography of the Armorial Orchestra and the Orange Group. Bibliographical sources, scientific journals and databases were also consulted. We consider Cussy de Almeida Neto a great musical influence. In Pernambuco, he brought together the most important composers of the Northeast and together they produced the first concert music with a Northeastern aesthetic for the Armorial Orchestra.